The Black-White achievement gap: Do state policies matter? - Henry I. Braun; Aubrey Wang; Frank Jenkins; Elliot Weinbaum (Arizona State University, 2006)
A longstanding issue in American education is the gap in academic achievement between majority and minority students. The goal of this study is to accumulate and evaluate evidence on the relationship between state education policies and changes in the Black-White achievement gap, while addressing some of the methodological issues that have led to differences in interpretations of earlier findings. To that end, we consider the experiences of ten states that together enroll more than forty percent of the nation's Black students. We estimate the trajectories of Black student and White student achievement on the NAEP 8th grade mathematics assessment over the period 1992 to 2000, and examine the achievement gap at three levels of aggregation: the state as a whole, groups of schools (strata) within a state defined by the SES level of the student population, and within schools within a stratum within a state. From 1992 to 2000, at every level of aggregation, mean achievement rose for both Black students and White students. However, for most states the achievement gaps were large and changed very little at every level of aggregation. The gaps are pervasive, profound and persistent. There is substantial heterogeneity among states in the types of policies they pursued, as well as the coherence and consistency of those policies during the period 1988-1998. We find that states' overall policy rankings (based on our review of the data) correlate moderately with their record in improving Black student achievement but are somewhat less useful in predicting their record with respect to reducing the achievement gaps. States' rankings on commitment to teacher quality correlate almost as well as did the overall policy ranking. Thus, state reform efforts are a blunt tool, but a tool nonetheless. Our findings are consistent with the following recommendations: states' reform efforts should be built on broad-based support and buffered as much as possible from changes in budgets and politics; states should employ the full set of policy levers at their disposal; and policies should directly support local reform efforts with proven effectiveness in addressing the experiences of students of different races attending the same schools.